Nets, puzzles, and postmen : An exploration of mathematical connections - Higgins, Peter M. (Oxford University Press, 2007)
What do railways, mingling at parties, mazes, and the internet all have in common? All are networks - people or places or things that connect to one another. Peter Higgins shows that these phenomena - and many more - are underpinned by the same deep mathematical structure, and how this understanding gives us remarkable new insights into the world. - ;What do road and railway systems, electrical circuits, mingling at parties, mazes, family trees, and the internet all have in common?. All are networks - either people or places or things that relate and connect to one another. Only relatively rec. The mathematics of networks form the basis of many fascinating puzzles and problems. This text shows how such puzzles, as well as many real-world phenomena, are underpinned by the same deep mathematical structure.